An International Continence Society (ICS) report on the terminology for female pelvic floor fistulas. Issue 8 (17th October 2020) - Goh, Judith; Romanzi, Lauri; Elneil, Sohier; Haylen, Bernard; Chen, Grace; Ghoniem, Gamal; Ijaiya, Munir'deen; Kwon, Soo; Lee, Joseph; Mourad, Sherif; Ramanah, Rajeev; Regmi, Mohan; et al.
Abstract: Introduction: The terminology for female pelvic floor fistulas (PFF) needs to be defined and organized in a clinically based consensus Report. Methods: This Report combines the input of members of the International Continence Society (ICS) assisted at intervals by external referees. Appropriate core clinical categories and a sub‐classification were developed to give a coding to definitions. An extensive process of 19 rounds of internal and external review was involved to examine each definition, with decision‐making by collective opinion (consensus). Results: A terminology report for female PFF, encompassing 416 (188 NEW ) separate definitions, has been developed. It is clinically based with the most common diagnoses defined. Clarity and user‐friendliness have been key aims to make it interpretable by practitioners and trainees in different specialty groups involved in female pelvic floor dysfunction and PFF. Female‐specific imaging (ultrasound, radiology, and magnetic resonance imaging) and conservative and surgical PFF managements as well as appropriate figures have been included to supplement and clarify the text. Interval (5–10 years) review is anticipated to keep the document updated and as widely acceptable as possible. Conclusion: A consensus‐based terminology report for female PFF has been produced to aid clinical practice and research.